Modern approaches to the management of multidisciplinary business - S. E. Bochkov (Путеводитель предпринимателя)
The scientific work is devoted to the consideration of management methods of multidisciplinary organizations aimed at adapting to dynamic market conditions. The main attention is paid to the issues of integrating digital technologies, improving internal processes, and improving the efficiency of interaction between departments. The article examines the experience of large international companies such as Amazon, Johnson & Johnson, Alphabet. Diversification, the use of a project approach, and the use of digital tools allow these organizations to achieve strategic goals. The implementation of ERP systems, the practical use of blockchain, the operation of Business Intelligence platforms, and the transition to flexible management models are analyzed. These approaches help to improve the coordination of work and optimize processes. The data show that the combination of network structures with elements of centralized management facilitates the introduction of modern technologies and contributes to an effective response to changes. A significant aspect is the implementation of corporate educational programs, the organization of cross-functional interaction that strengthens professional ties. Scientific articles were used as sources, as well as materials that are publicly available on the Internet. The conclusions of the article emphasize the need to switch to modern management technologies, abandon outdated solutions to ensure the effective operation of multidisciplinary enterprises. The materials of the scientific work are addressed to the heads of companies, experts in the field of corporate governance, scientists studying complex organizational structures.